Adherence to malaria treatment guidelines among health care workers in private health facilities in Kampala's informal settlements, Uganda. - Douglas Bulafu; Bridget Nagawa Tamale; Lesley Rose Ninsiima; James Natweta Baguma; Lydia Nabawanuka Namakula; Filimin Niyongabo; Grace Biyinzika Lubega; Dickson Aruhomukama; Rawlance Ndejjo; David Musoke (Public Library of Science (PLoS), 2023)
Poor adherence to malaria treatment guidelines among healthcare workers (HCWs) is a major contribution to diagnostic challenges, treatment failure, and non-rational use of antimalarial medicines. However, there is limited information about adherence to malaria treatment guidelines among HCWs in private health facilities in informal settlements in Uganda. This study therefore assessed the level of adherence to malaria treatment guidelines and associated factors among HCWs in private health facilities in Kampala's informal settlements. A cross-sectional study was conducted among 339 HCWs from private health facilities in slums of 4 selected divisions in Kampala, Uganda. Quantitative data was collected using a semi-structured questionnaire, cleaned in MS Excel 2016 and analyzed using STATA 15.0 statistical software. Bivariate and multivariate analysis were conducted using a generalized linear model of modified Poisson regression to obtain factors associated with adherence to malaria treatment guidelines. The study revealed that majority of respondents 71.1%(241/339) were aged 30 years and below, and 50.1%(170/339) of the were female. Almost all of the respondents 98.8%(335/339) reported that they had malaria diagnostic equipment (microscopy or rapid diagnostic tests) at their facilities, 47.5%(161/339) had non-recommended anti-malarial drugs present in stock and 36.0% reported that they did not refer severely ill patients to higher health facilities in the previous 3 months. Although 92.6%(314/339) of the respondents had heard about the national malaria treatment guidelines, 63.1%(214/339) of them adhered to these guidelines. Having a bachelors degree (APR 1.54, (CI: 1.13-2.10)P 0.006), and having high levels of knowledge (APR 1.44, (CI: 1.13-1.60)P 0.001) were positively associated with high adherence to malaria treatment guidelines. In conclusion, adherence to malaria treatment guidelines was suboptimal and less than the national target of 90%. Enforcement, supervision, trainings, and continuous medical education should be enhanced in private healthcare facilities to improve adherence to malaria treatment guidelines in informal settlements.